PENGENALAN PENGHITUNGAN HARGA POKOK PRODUKSI BAGI SISWA SMA RICI - Lukman, Hendro; Darwis, Andrea Stephanie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Cost of Goods Manufatured is an important part of a manufacturing or producer business. Calculating the Cost of Goods Production using the wrong method will have an impact on determining the selling price of the product, which will ultimately affect the profit of the company or business. The topic